JUDICIAL REVIEW TERHADAP PERATURAN MENTERI KEUANGAN NOMOR 58 TAHUN 2023 TENTANG TARIF PEMOTONGAN PPH PASAL 21 ATAS PENGHASILAN WAJIB PAJAK ORANG PRIBADI MELALUI KEWENANGAN HAK UJI MATERI MAHKAMAH AGUNG (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The Minister of Finance Regulation Number 58 of 2023 on Income Tax Article 21 deductions aims to simplify income tax calculation and administration through the application of the Average Effective Rate (TER). However, its implementation has sparked public debate, especially regarding the taxation of religious holiday allowances (THR) and bonuses, which impact employee take-home pay in December. This study aims to analyze the impact of the regulation on individual taxpayers and evaluate the urgency of submitting a judicial review to the Supreme Court through material review authority. A descriptive qualitative approach is employed using library research and normative juridical analysis of tax regulations and legal literature. The findings indicate that while the TER system simplifies tax administration, applying it to non-regular income such as THR may impose a heavier burden on employees. Thus, policy evaluation is necessary to ensure fairness and legal protection for taxpayers through available judicial mechanisms.